Oxidative response to Cd and Pb accumulation in coastal fishes of Pattani Bay - Phanwimol Tanhan; Kanjana Imsilp; Niyada Lansubsakul; Wachiryah Thong-asa (Italian Journal of Animal Science)
Bioaccumulation of heavy metals can cause physiological and biochemical alterations in aquatic animals. Accumulation of Cd and Pb and oxidative response in the liver and muscle of fish species; Scatophagus argus, Plotosus lineatus, Netuma thalassina and Mugil cephalus were evaluated. Accumulation of Cd, Pb and oxidative response indicated by malondialdehyde (MDA) were significantly higher in the liver than muscle in all coastal fish species. Antioxidative parameters, such as reduced glutathione (GSH), catalase (CAT), and superoxide dismutase (SOD), varied. S. argus exhibited the highest levels of Cd and Pb accumulation, both in the liver and muscle. Simultaneous activation and depression of oxidative defense mechanism was depicted in S. argus’s liver which indicated by positive correlation of Pb to CAT activity and negative correlation of Pb to SOD activity. Positive correlation was significance for Cd and Pb accumulation in the liver and muscle of M. cephalus, which may be used for pollution biomonitoring. The present study indicated the oxidative response to Cd and Pb accumulation was emphasise in liver, while oxidative response varied in each coastal fish species.Highlights Accumulation of Cd, Pb, and oxidative status, i.e., lipid peroxidation level indicated by malondialdehyde (MDA), was significantly higher in the liver than muscle in 4 coastal fish species (Scatophagus argus, Plotosus lineatus, Netuma thalassina, and Mugil cephalus). S. argus exhibited the highest levels of Cd and Pb accumulation, both in the liver and muscle, when compared to other three coastal fish species. The liver’s oxidative response to Pb was high in S. argus, and represented simultaneous activation and depression of antioxidative defense mechanism. A significant positive correlation was revealed for Cd and Pb accumulation in the liver and muscle of M. cephalus, which may be used for pollution biomonitoring.